Need Analysis in The Development of HOTS-Oriented Study Project Assesment Instrument in Android-Based Science Learning - Handayani, Fitri; Hartono, Hartono; Lestari, Wahyu (Universitas Negeri Semarang, 2019)
Need analysis in the development of HOTS-oriented project assesment instruments on Android-based Science learning was carried out with the aim of identifying teacher need about HOTS-oriented project assesment instruments in the form of modules and Android applications. The problem found by researchers is project assessment on Science learning heat transfer material is not HOTS-oriented and proven when observation, the assessment book only assesses two indicators, namely the completeness of the tools and materials and the suitability of the trial and step. Two indicators are not enough to assess project skills and have not been able to measure the ability of the students’ HOTS, so teachers need the development of HOTS-oriented project assessment instruments on Android-based Science learning. Android application made with simple codding. The method used for research is research and development (R&D). Qualitative data analysis is used to describe triangulation of data sources, while quantitative data analysis is used to test validity, reliability and practicality. The results of the need analysis of 20 statement items filled by fifth grade teachers in the Sunan Kalijaga Cluster of Gemuh Subdistrict to 8 teachers obtained validity, each statement item was greater than r-table, 0.707 and was declared to be valid. Reliability obtained 0.973 and declared to be reliable. It is hoped that modules and Android applications will be available which can be accessed through Google Drive. The practicality of the module is carried out after the instrument is valid and reliable. Teachers can use HOTS-oriented project assessment instrument manuals on Andoid-based Science learning in classroom learning.